Faktor - Faktor yang Mempengaruhi Kinerja Pegawai pada Badan Penanggulangan Bencana Daerah Kota Solok - Esi Sriyanti; Seflidiana Roza; Rahmadina Rahmadina (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to examine the influence of rewards and competence on employee performance at the Solok City Regional Disaster Management Agency, using a quantitative approach with a sample of 64 respondents. Based on the t-test results for variable X1 (Reward), the t-value of 0.884 is lower than the t-table value of 1.999, and the significance level of 0.380 exceeds 0.05, indicating that the reward variable does not significantly affect employee performance (Y). Meanwhile, for variable X2 (Competence), the t-value of 4.529 exceeds the t-table value of 1.999, and the significance level of 0.000 is below 0.05, showing that competence has a significant effect on employee performance. The F-test analysis reveals an F-value of 16.368, which is higher than the F-table value of 3.15, meaning that both Reward (X1) and Competence (X2) collectively influence employee performance. Additionally, the R Square value of 0.349 indicates that 34.9% of employee performance can be explained by Reward and Competence, while the remaining 65.1% is influenced by other variables not covered in this research.